2021
DOI: 10.1007/s00162-021-00571-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroelastic interaction of nonlinear waves with floating sheets

Abstract: Hydroelastic responses of floating elastic surfaces to incident nonlinear waves of solitary and cnoidal type are studied. There are N number of the deformable surfaces, and these are represented by thin elastic plates of variable properties and different sizes and rigidity. The coupled motion of the elastic surfaces and the fluid are solved simultaneously within the framework of linear beam theory for the structures and the nonlinear Level I Green–Naghdi theory for the fluid. The water surface elevation, defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 62 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…In Figure 4a, the comparison shows that the trend of C t is in a similar pattern however, there are some deviations between the two models. This is because of the nonlinearity in [26] and the linearity in the present BIEM model. From Figure 4b,c, it is found that the trend of the C r and C t are similar and also the data between the BIEM and SWA are very close to each other.…”
Section: Comparison Of Results With Existing Published Results Experimental Datasets and Swa Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In Figure 4a, the comparison shows that the trend of C t is in a similar pattern however, there are some deviations between the two models. This is because of the nonlinearity in [26] and the linearity in the present BIEM model. From Figure 4b,c, it is found that the trend of the C r and C t are similar and also the data between the BIEM and SWA are very close to each other.…”
Section: Comparison Of Results With Existing Published Results Experimental Datasets and Swa Modelmentioning
confidence: 99%
“…(a) Comparison of the t C : present (BIEM) and Green-Naghdi model [26]. Comparison of the deflection amplitude with the model [24] and experimental data in [25].…”
Section: Comparison Of Results With Existing Published Results Experimental Datasets and Swa Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…which can be written both under the free surface in RI and under the sheet in RII. Pressure distribution in both regions can be obtained from Euler's equation in the form [22]:…”
Section: (A) the Green-naghdi Equationsmentioning
confidence: 99%
“…The present study is the first attempt to build a theoretical model of wave-and current-induced drift of an elastic plate of arbitrary length, elasticity and thickness and provide insight about the fluid and structure dynamics. In our recent work [22], we have considered the interaction of nonlinear waves with a set of elastic plates, restricted to the vertical motion. In this paper, we will study wave and current interaction with a floating elastic sheet, which is free to drift horizontally.…”
Section: Introductionmentioning
confidence: 99%